A comparison of Monte Carlo, anisotropic analytical algorithm (AAA) and Acuros XB algorithms in assessing dosimetric perturbations during enhanced dynamic wedged radiotherapy deliveries in heterogeneous media. Issue 1 (6th August 2018) - Zaman, Ashfaq; Kakakhel, Muhammad Basim; Hussain, Amjad
Abstract: Background: A comparison of anisotropic analytical algorithm (AAA) and Acuros XB (AXB) dose calculation algorithms with Electron Gamma Shower (EGSnrc) Monte Carlo (MC) for modelling lung and bone heterogeneities encountered during enhanced dynamic wedged (EDWs) radiotherapy dose deliveries was carried out. Materials and methods: In three heterogenous slab phantoms: water–bone, lung–bone and bone–lung, wedged percentage depth doses with EGSnrc, AAA and AXB algorithms for 6 MV photons for various field sizes (5×5, 10×10 and 20×20 cm 2 ) and EDW angles (15°, 30°, 45° and 60°) have been scored. Results: For all the scenarios, AAA and AXB results were within ±1% of the MC in the pre-inhomogeneity region. For water–bone AAA and AXB deviated by 6 and 1%, respectively. For lung–bone an underestimation in lung (AAA: 5%, AXB: 2%) and overestimation in bone was observed (AAA: 13%, AXB: 4%). For bone–lung phantom overestimation in bone (AAA: 7%, AXB: 1%), a lung underdosage (AAA: 8%, AXB: 5%) was found. Post bone up to 12% difference in the AAA and MC results was observed as opposed to 6% in case of AXB. Conclusion: This study demonstrated the limitation of the AAA (in certain scenarios) and accuracy of AXB for dose estimation inside and around lung and bone inhomogeneities. The dose perturbation effects were found to be slightly dependent on the field size with no obvious EDW dependence.